UPAYA PENINGKATAN KUALITAS PENDIDIKAN DENGAN PENERAPAN KEDISIPLINAN GURU DI SD MUHAMMADIYAH 9 “PANGLIMA SUDIRMAN” MALANG - Ayu Agustin; Muhammad Hasyim Ashari (Sekolah Tinggi Ilmu Ekonomi AMA, 2023)
As an effort to improve the quality of education is the discipline of teachers. Increasing teacher discipline in the teaching and learning process is expected to improve the quality and quality of education in order to give birth to the next generation who are superior and have good morals. This community service activity was carried out at SD Muhammadiyah 9